Digital Agri Co-Lab: Fostering research, collaboration & skills for enabling digital innovation in agri-food systems - Nagaraji, Satish; Gardeazabal Monsalve, Andrea; Gopalan, Padmavati (CGIAR, 2023)
Digital innovation continues to offer opportunities for a transformative shift in the Global South's agrifood sector, but it also faces significant challenges. Known for its diverse agricultural practices and smallscale farming, the Global South requires customized solutions to enhance productivity and sustainability and ensure scaling. Obstacles like the increasing digital divide, weak information systems and infrastructure, and limited digital capabilities, particularly among marginalized rural populations, hinder progress. This white paper highlights why and how collaboration is required among diverse stakeholders, systems and digital solutions to address key emerging challenges such as interoperability, standardization, data privacy and ethics in AI. The Co-Lab (https://co-lab.cgiar.org), a collaborative platform developed by the Digital Innovation Initiative of CGIAR, could help overcome these problems. Co-Lab is designed to catalyze innovation in the agricultural and food sectors through collaboration and partnership, addressing key issues like lack of experimental spaces, validation processes, and knowledge sharing. Its primary objective is to co-create impactful, context-specific solutions that resonate with the unique needs of agricultural systems, particularly in the Global South. The Co-Lab platform's unique approach aims to bridge existing gaps in digital innovation by promoting a collaborative environment for the actors. In this space, different actors, including AgTech companies, private sector entities, governments, research institutes, academic institutes, civil society organizations and farmer organizations, can come together to leverage their collective expertise to address shared challenges in the agricultural ecosystem. By fostering a culture of peer-to-peer knowledge exchange, Co-Lab enables stakeholders to share insights, experiment, collaborate and validate new ideas, thereby avoiding the pitfalls of working in isolation. Through its efforts, Co-Lab aspires to overcome the fragmentation in digital innovation, paving the way for a more cohesive, collaborative, and impactful transformation of agri-food systems in the Global South. Co-Lab’s vision is embodied in its structure, featuring four foundational pillars: a virtual collaborative space that facilitates robust discussions and the sharing of ideas; an innovation repository acting as a comprehensive directory of the latest digital agricultural technologies; a Digital Innovation Navigation Assistant (DINA), an advanced tool powered by Generative AI, that guides stakeholders through the complex terrain of agricultural technologies; and a Learning Network dedicated to capacity development through tailored training courses offered both online and via WhatsApp Bots. Through its comprehensive approach and commitment to inclusivity, Co-Lab will be a key driver in the digital transformation of agrifood systems in the regions of the Global South.